Validity evidence of the Self-Care of Chronic Illness Inventory: Brazilian version - Mariana Tereza Monferdini Ruoco Acettia; Michele Nakahara-Melo; Fernanda Ayache Nishi; Dina Almeida Lopes Monteiro Cruz (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To generate evidence regarding the validity of the internal structure and consistency of the Self-Care of Chronic Illness Inventory - Brazilian Version and its relationship with health-related quality of life. Method: A psychometric study of instrument validation was carried out with 227 adults (female=74.89%; mean age= 58.03±13.2 years) with chronic illnesses who answered the instrument adapted for Brazil. Internal structural validity was studied by confirmatory factor analysis, the relationship with health-related quality of life was analyzed by correlation with health-related quality of life, and internal consistency by the omega coefficient. Results: The theoretical structure of the instrument was confirmed with three domains and good fit indexes and 18 of the 20 items had factorial loadings above 0.3; the omega coefficient was 0.929; and participants with better self-care scores had better quality of life scores. Conclusion: The Self-Care of Chronic Illness Inventory - Brazilian Version provides good evidence of internal validity and consistency for studying self-care in chronic diseases in Brazil.